A qualitative investigation of coaching mental model of expert rowing coaches in Japan - Kitamura, K.; Suzuki, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The exceptional levels of coaching require certain types of environmental support, special experiences, and appropriate motivational encouragement (Salmela, 1994). In this context, Salmela suggested that the most important role of the coach is to make the athletes center their efforts upon deliberate practice and to minimize the resource, effort and motivational constraints which impede the skill development of the athletes (Salmela, 1994). The purpose of this study was to explore the coaching mental model of expert rowing coaches in Japan. Methods: Participant selection was limited to expert coaches who had the coaching experience of Japanese national rowing team. Six coaches served as participants for this study. Their average age was 36.3 years old, and they had an average of 9.7 years of coaching. In-depth, open-ended interviews were conducted with each coach. Interviews raged between 60 to 90 minutes, were recorded with the permission of the participants. The interviews were systematically transcribed verbatim immediately after the completion of each interview, and total of 473 meaning units were extracted from the data set. The data was decontextualized using an inductive procedure for analyzing unstructured qualitative data (Côté, Salmela, Baria, & Russell, 1993). Results: The inductive analysis process resulted in regrouping these interview transcripts into three categories (continuous self-change through a reflection, focus on a learning process, and orientation toward self-growth), and eight sub-categories (attaching meaning to awareness, self-accept, vision, rationalization, feedback, communication, self-determination, and self-coaching). Discussion: All of the participants faced a lot of problems and built up their unsuccessful experiences throughout their coaching career. Consequently they realized the needs of continuous self-change to develop their coaching expertise. Evidence of the coaches` mental conflicts to the coaching activities with athletes also surfaced throughout the training and race. This study found significant agreement between the perceptions of the concepts on how coaches evaluated their coaching activities in relation to performance enhancement of athletes and how this support affected their development of coaching excellence. The strong relationship between three categories indicates that coaches construct the practice environment in a manner that maximizes athletes` commitment to daily effortful practice.